Aldosterone to Renin Ratio (ARR) in Clinical use, with Reference to the Primary Care Setting: ARR to Whom, When, How, What for? - Olivieri, Oliviero; Pizzolo, Francesca; Corrocher, Roberto (Current Hypertension Reviews, 2008)
Compelling evidence indicates that primary aldosteronism (PA) is the most frequent cause of secondary hypertension, with an estimated prevalence ranging from 10 to 15% in the population referred to specialist hypertension units. In clinical practice, the aldosterone to renin ratio (ARR) is the cornerstone of population screening, although difficulties in methodology and thus in defining precise cut-off values still represent an area of uncertainty. In hypertensive subjects, the elevated ARR is a marker of inappropriately high aldosterone secretion for the degree of renin-angiotensin system activation, and often is the only index capable of distinguish normokalemic PA from essential hypertension. On the basis of such a high prevalence, it is unclear whether ARR measurement should be reserved for selected subgroups of patients, or extended to all hypertensive subjects in the population as a whole. In unselected, normotensive populations elevated aldosterone levels and elevated ARR have recently been reported as predisposing factors to the subsequent development of hypertension, raising the question of the optimal timing for ARR measurement, especially in those with a family history of hypertension in primary care. In a large proportion of patients presenting elevated ARR the diagnosis of PA is formally ruled out by confirmatory/ exclusion testing, although the clinical relevance of “inappropriate aldosterone secretion” in these patients remains unclear. May it serve as a predictor of the usefulness of mineralocorticoid receptor antagonist treatment? These and related questions will be examined in this review, particularly given clearly unsatisfactory levels of BP control even in the populations of Western countries.
Keywords: renin